2017
DOI: 10.3389/fnmol.2017.00174
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Chemotherapy-Induced Peripheral Neuropathy

Abstract: Chemotherapy-induced neuropathy is a common, dose-dependent adverse effect of several antineoplastics. It can lead to detrimental dose reductions and discontinuation of treatment, and severely affects the quality of life of cancer survivors. Clinically, chemotherapy-induced peripheral neuropathy presents as deficits in sensory, motor, and autonomic function which develop in a glove and stocking distribution due to preferential effects on longer axons. The pathophysiological processes are multi-factorial and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
423
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 472 publications
(440 citation statements)
references
References 239 publications
(337 reference statements)
9
423
0
8
Order By: Relevance
“…As shown in the prevention protocol involved in our study, in oxaliplatin-treated mice, duloxetine attenuated the development of early-phase cold allodynia, but it had no prophylactic effect against the development of late-phase allodynia. This finding seems to confirm that the development of early-phase and late-phase CIPN in oxaliplatin-treated mice might be mediated by distinct mechanisms (Furgała, Fijałkowski, et al, 2018;Sałat et al, 2019;Starobova & Vetter, 2017). Of note, in this prevention protocol, we noted decreased latencies to pain reaction in vehicle-treated non-neuropathic mice on day 7.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As shown in the prevention protocol involved in our study, in oxaliplatin-treated mice, duloxetine attenuated the development of early-phase cold allodynia, but it had no prophylactic effect against the development of late-phase allodynia. This finding seems to confirm that the development of early-phase and late-phase CIPN in oxaliplatin-treated mice might be mediated by distinct mechanisms (Furgała, Fijałkowski, et al, 2018;Sałat et al, 2019;Starobova & Vetter, 2017). Of note, in this prevention protocol, we noted decreased latencies to pain reaction in vehicle-treated non-neuropathic mice on day 7.…”
Section: Discussionsupporting
confidence: 84%
“…There is a large body of evidence showing that oxaliplatin induces two forms of neuropathy-acute and chronic (reviewed in Starobova & Vetter, 2017), and these two phases are thought to be mediated by distinct mechanisms: altered neuronal excitability, TRPA1 channel activation (Nakagawa & Kaneko, 2017), impaired calcium homeostasis-all involved mainly in the development of the early phase, and mitochondrial dysfunction, glial cell activation, oxidative stress, axon degeneration, neuroinflammation underlying the late one (Nakagawa & Kaneko, 2017;Sisignano et al, 2014;Starobova & Vetter, 2017). Therefore, the efficacy of analgesics used for pain relief in these two phases of CIPN might be also different (Furgała, Fijałkowski, et al, 2018;Sałat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not identify risk factors predisposing patients to peripheral neuropathy. For example, age did not influence vincristine‐induced neuropathy as it did in other studies . Prior treatment may predispose to peripheral neuropathy but no patients in this cohort received other chemotherapeutic agents before initiating CV .…”
Section: Discussionsupporting
confidence: 45%
“…Despite the fact that Previous studies have shown that most patients develop some degree of peripheral neuropathy at a cumulative dose of more than 4 mg/m 2 . 17,18 In our study, patients developed peripheral neuropathy after receiving, on average, a cumulative dose of 2.90 mg/m 2 of vincristine, suggesting that the intensity of vincristine infusion during induction increases the risk of developing neuropathy. Neurotoxicity was most marked during induction, but decreased during the maintenance phase of therapy in tandem with reduced vincristine intensity.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation